Stressful Life Events, Cognitive Biases, and Symptoms of Depression in Young Adults - Łosiak, Władysław; Blaut, Agata; Kłosowska, Joanna; Łosiak-Pilch, Julia (Frontiers in Psychology, 2019)
Although the link between stressful experiences and depression has been supported in numerous studies, the specific mechanisms of this relationship are still unclear. Cognitive theories of depression postulate that the influence of stress on depression may be modified by cognitive factors. The aim of the present study was to examine the interplay between negative life events, cognitive vulnerability factors, and depressive symptoms. It was hypothesized that the relationship between negative life events and symptoms of depression is shaped by rumination and cognitive biases. The study sample consisted of 108 young adults (19 men and 89 women; M=20.31; SD =1.84). Memory bias and attentional bias were assessed using the Attentional Blink Task and the Memory Task, respectively. Rumination and depressive symptoms were assessed via self-report questionnaires. Logistic regression and moderation analyses were conducted to examine the relationship between the study variables. Stressful life events, rumination and memory bias were found to be significantly related to depressive symptoms. Moderation analyses revealed that there is a positive relationship between negative life events and depressive symptoms but only among individuals characterized by an elevated level of rumination and among participants exhibiting negative attentional bias. The results provide further evidence for cognitive models of depression.